Pulse co-deposition of tin-silver alloy from citric acid plating bath for microelectronic applications - Sharma, Ashutosh; Chung, Choong Heui; Ahn, Byungmin (Materials Research Express, 2019)
Sn-Ag alloys are gaining importance among microelectronics manufacturers because of their potential benefits, e.g., low melting point, excellent wetting to common metallic substrates, and superior mechanical properties required for microelectronic packaging devices. In this work, Sn-Ag alloy was co-deposited from acidic citric acid bath on copper substrates. The plating solution was composed of SnSO4, Ag2SO4, thiourea, and citric acid as a supporting electrolyte. Further, the influence of current density on the Ag content of the coatings was studied. The results indicate that the citric acid bath produces bright Sn-Ag deposits over a wide range of current densities. The grains of the deposits obtained were bigger at lower current densities (10-30 mA cm-2) and become finer at higher current densities (40-50 mA cm-2). Initially, the coatings were very hard and become soft as the current density increases gradually due to the decreased amount of Ag in the deposit which modified the coating solderability.
Keywords: Lead-Free; Low melting point; Metallic substrate; Microelectronic applications; Microelectronic packaging; Plating solutions; Potential benefits; Supporting electrolyte; current density; lead-free; microelectronics; plating; solder; tin